STUDY SOME VIRULENCE FACTORS OF ASPERGILLUS SPP THAT ISOLATED FROM CANCER PATIENTS WHO ARE SUFFERING FROM CHEST RESPIRATORY DISEASE - Faiza Majid Najm; Sanaa Hussein Mohammed (Scholar Express Journals, 2022)
The present study was designed to Isolation and diagnosis of Aspergillus species from cancer patients. A total of two hundred fifty-six (256) were collected from patients (sputum sample), aged between
Keywords: Aspergillus; protease; urease; virulence factors